SURFACE OXIDATION OF PYRITE UNDER AMBIENT ATMOSPHERIC AND AQUEOUS (PH = 2 TO 10) CONDITIONS: ELECTRONIC STRUCTURE AND MINERALOGY FROM X-RAY ABSORPTION SPECTROSCOPY - Todd E.C.; Sherman D.M.; Purton J.A. (My University, 2003)
The nature of the surface oxidation phase on pyrite, FeS2, reacted in aqueous electrolytes at pH = 2 to 10 and with air under ambient atmospheric conditions was studied using synchrotron-based oxygen K edge, sulfur LIII edge, and iron LII,III edge X-ray absorption spectroscopy. We demonstrate that O K edge X-ray absorption spectra provide a sensitive probe of sulfide surface oxidation that is complementary to X-ray photoelectron spectroscopy. Using total electron yield detection, the top 20 to 50 Α of the pyrite surface is characterized. In air, pyrite oxidizes to form predominantly ferric sulfate. In aqueous air-saturated solutions, the surface oxidation products of pyrite vary with pH, with a marked transition occurring around pH 4. Below pH = 4, a ferric (hydroxy)sulfate is the main oxidation product on the pyrite surface. At higher pH, we find iron(III) oxyhydroxide in addition to ferric (hydroxy)sulfate on the surface. Under the most alkaline conditions, the O K edge spectrum closely resembles that of goethite, FeOOH, and the surface is oxidized to the extent that no FeS2 can be detected in the X-ray absorption spectra. In a 1.667 x 10-3 mol/L Fe3+ solution with ferric iron present as FeCl3 in NaCl, the oxidation of pyrite is autocatalyzed, and formation of the surface iron(III) oxyhydroxide phase is promoted at low pH.
Keywords: pyrite